Effects of Functional Red Pine Seed Direct-Drinking Oil on Constipation and Intestinal Barrier Function in Mice - Jie Li; Haonan Zheng; Jiahui Liu; Jie Ding; Qingqi Guo; Na Zhang (Antioxidants)
Constipation is a prevalent global health issue that greatly affects human well-being. However, many existing treatments are associated with side effects, necessitating the development of alternative approaches. In this study, a balanced fatty acid red pine seed direct-drinking oil (SFA:MUFA:PUFA = 1.14:1.08:1, n − 6:n − 3 = 4.17:1) was formulated using red pine seed oil as the base oil, blended with coconut oil, rice bran oil, and camellia oil. The study investigated the effects and mechanisms of this red pine seed direct-drinking oil in alleviating constipation in mice. Results showed that, compared to normal mice, constipated mice exhibited symptoms of dry stools, difficulty defecating, abnormal neurotransmitter levels, oxidative stress, and colonic tissue damage. Additionally, the protein expression levels of occludin and claudin-1 were reduced by 86.11% and 25.00%, respectively (p < 0.05), while mRNA expression levels decreased by 70.80% and 59.00% (p < 0.05). Red pine seed direct-drinking oil intake improved defecation, reduced serum levels of vasoactive intestinal peptide (VIP), endothelin-1 (ET-1), and nitric oxide (NO), and increased substance P (SP) levels. Furthermore, it also significantly elevated serum levels of superoxide dismutase (SOD) and catalase (CAT) (p < 0.05), alleviated colonic tissue damage, and upregulated the protein and mRNA expression levels of occludin and claudin-1 (p < 0.05). These findings suggest that red pine seed direct-drinking oil alleviates constipation in mice by enhancing intestinal motility, regulating serum neurotransmitters, mitigating oxidative stress, repairing intestinal barrier damage, and increasing tight junction protein expression. This study represents the first use of red pine seed direct-drinking oil to alleviate constipation in mice, providing a novel approach to improving symptoms in individuals with constipation.